Budgetstyrning i praktiken : En fallstudie av Luleå tekniska universitet - Keskitalo, Ann-Marie; Markgren, Lisbet (2013)
We have studied the use of budgets for planning and control purposes in a public organization. The objective of the study was to explore if and how the view of budgets varies from strategic-tactic level to operative level. A single case study was conducted at Lulea University of Technology. The empirical material was collected with interviews of six employees representing different levels in the organization. The result of the study shows that the view of budgets varies more depending on type of operation than on the level of organization that the interviewees represent. All interviewees agree that the budget is of significant value for planning and it is also important for the on-going dialog and budget monitoring. However, the budget was not used for control purposes. That can be dependent on the different conditions that are the case for different operations at the university, teaching and research. There is also a built-in confusion regarding accountability in the delegation of authority. The use of budget for control purposes is most obvious when it comes to funds for strategic investments. Several interviewees proposed improvements in the budgetary process. One conclusion of the study is that there seems to be good opportunities for improvements in the budgetary process of the studied organization as long as processes and tools are designed for the different operations. Validerat; 20130813 (global_studentproject_submitter)